SOSIALISASI PEMANFAATAN APLIKASI ANDROID SDGs DESA UNTUK EFISIENSI WAKTU DALAM PENGINPUTAN DATA PENDAPATAN MASYARAKAT DESA NOGO REJO - Permata Selly Pasa Hartiah; Haidir Lubis; Annisa Rizkia (Cattleya Darmaya Fortuna, 2022)
The specific goals and targets of this community service activity are intended for hamlet heads and part of the community located in Nogo Rejo Village, Galang District, Deli Serdang Regency. The advantage of using this village SDGs Android application is that it streamlines community data input time. Previously, the head of the village conducted data collection using paper anvid re-entered it with the village SDGs Android application. Thus,socialization is needed so that parties participating in the socialization can directly help input data directly into the village SDGs Android Application without using data collection paper again. This service activity are: (1) Collecting problems faced by partners (2) Finding the best solution to the conditions faced (3) Conducting sosialization to solve problems faced by partners (4) Making reports on socialization activities as a form of accountability